(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The catalogue of threats which currently exist in the national security environment and may occur in the future is constantly growing. These phenomena are characterized by diversity, intensity, as well as unpredictability of the scale and consequences of their occurrence. The diversity of threats results from the fact that they are a consequence of mutually interacting political, military, economic and social, demographic and environmental processes and phenomena. Their paper causes that they increasingly often lead to the occurrence of a crisis situation, and thus to the disruption of the normal functioning of the state. The article attempts to analyze the specific determinants of national security.